(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Data on 55 lichen species (namely Absconditella lignicola Vězda & Pišut, Agonimia tristicula (Nyl.) Zahlbr., Anisomeridium polypori (Ellix et Everh.) M.E. Barr, Arthopyrenia salicis A. Massal., Arthonia ilicina Taylor, A. vinosa Leight., Bacidia circumspecta (Nyl. ex Vainio) Malme, Biatora chrysantha (Zahlbr.) Printzen, B. epixanthoides (Nyl.) Diederich, Catillaria alba Coppins & Vězda, C. erysiboides (Nyl.) Th. Fr., Cladonia norvegica Tønsberg & Holien, Diploschistes gypsaceus (Ach.) Zahlbr., Eopyrenula avellanae Coppins, Fellhanera subtilis (Vězda) Diederich & Sérusiaux, Fuscidea arboricola Coppins & Tønsberg, F. cyatoides (Ach.) V. Wirth & Vězda var. corticola (Fr.) Kalb, F. pusilla Tønsberg, Ropalospora viridis (Tønsberg) Tønsberg, Jamesiella anastomosans (P. James & Vězda) Lücking, Sérusiaux & Vězda, Hypocenomice caradocensis (Leighton ex Nyl.) P. James & G. Schned., H. xanthococca (Sommerf.) P. James & G. Schneider, Lecania cyrtellina (Ach.) Th. Fr., Lecanora cinereofusca Magnusson, L. farinaria Borrer in Hook., Lecidea swartzioidea Nyl., Lepraria lobificans Nyl., L. rigidula (B. de Lesd.) Tønsberg, Leproloma vouauxii (Hue) J.R. Laundon, Leptogium teretiusculum (Wallr.) J.R. Laundon, Leptorhaphis maggiana (A. Massal.) Korber, Megalaria pulverea (Borrer) Hafellner & E. Schreiner, Micarea adnata Coppins, M. hedlundii Coppins, M. melaeniza Hedl., M. nigella Coppins, M. peliocarpa (Anzi) Coppins & R. Sant., Mycoblastus sterilis Coppins & P. James, Microcalicium ahlneri Tibell, Ochrolechia szatalensis Verseghy, Pertusaria pupillaris (Nyl.) Th. Fr., Phaeophyscia endophoenicea (Harm.) Moberg, Ph. hirsuta (Mereschk.) Moberg, Physcia vitii Nadv., Porina leptalea (Durieu & Mont.) A.L. Sm., Ramonia chrisophaea (Pers.) Vězda, Reichlingia leopoldii Diederich & Scheidegger, Rinodina griseosoralifera Coppins, R. efflorescens Malme, Telocarpon strasseri Zahlbr., Shismatomma ricasolii (A. Massal.) Egea, Trapelia corticola Coppins & P. James, Trapeliopsis pseudogranulosa Coppins & P. James, Vezdaea aestivalis (Ohl.) Tsch.-Woess & Poelt, Zamenhofia hibernica (P. James & Swinscow) Clauz. & Roux) found in the territory of the recently created Uzhansky National Nature Park, Ukrainian part of the ‘Eastern Carpathian’ Trilateral Biosphere Reserve, which for the first time recorded for the whole Ukraine or Eastern Carpathians, are provided. Each taxon is provided by references on papers where full diagnosis is published, list of localities, taxonomical remarks and data on general distribution.